Childhood ADHD Symptoms in Relation to Trauma Exposure and PTSD Symptoms Among College Students: Attending to and Accommodating Trauma - Miodus, Stephanie; Allwood, Maureen A; Amoh, Nana (Journal of emotional and behavioral disorders)
Attention-deficit/hyperactivity disorder (ADHD) and posttraumatic stress disorder (PTSD) are highly comorbid among children and adolescents with a history of maltreatment and trauma. This comorbidity is linked to increased symptom severity and poor academic and social outcomes. Such negative outcomes are shown to have further negative outcomes during the college years. However, research has yet to directly examine the associations between ADHD, trauma exposure, and PTSD among college students. To address this gap, the current study examined the relations between childhood ADHD symptoms, lifetime trauma exposure, and current PTSD symptoms among a racially and ethnically diverse group of college students (N = 454). Analyses controlled for symptoms of depression and anxiety and examined demographic differences. Findings indicated that college students with a childhood history of elevated ADHD symptoms reported significantly higher numbers of trauma exposure and PTSD symptoms. Findings also indicated that trauma-related arousal symptoms and more general depressive symptoms were the strongest mediators in the association between ADHD symptoms and trauma exposure. These results have implications for child and adolescent clinical interventions, as well as for college counseling and accessibility services related to psychological well-being and academic accommodations.